Determinants of insurance companies' stock return in GCC countries - Al-Shami, Hamdan Ahmed Ali (2013)
This study examines the determinants of insurance companies’ stock returns in GCC stock markets using two models based on panel data over the period of 2001-2010. In the first model, monthly data for each of the GCC market were used to analyses the effect of macroeconomic variables (inflation, interest rate, money supply, oil prices and unemployment rate) on insurance index’ stock returns with stock market return as the control variable. In the second model, using annual data, firm specific variables (earning per share, dividend yield, leverage, loss ratio, reinsurance dependence, solvency margin, affiliated investment and stability of underwriting operation), macroeconomic variables (inflation, money supply, oil prices and unemployment rate) and stock market return are all modelled together into determining their effects on insurance companies’ stock returns. This study applied panel data estimation which includes pooled estimation, fixed effect panel estimation and random effect panel estimation to derive the most appropriate estimation. The results from the first model indicate four out of five macroeconomic indicators, namely inflation, money supply, oil prices and unemployment rate, are significant in affecting the insurance index returns in the GCC stock markets. The analyses using the second model reveal that only earning per share, dividend yield, leverage and solvency margin effect insurance companies’ stock returns significantly. This study contributes to the literature in terms of revealing the effect of a comprehensive set of economics, firm specific and insurance company specific factors on GCC’s Insurance companies’ stock returns based on robust analyses. The research findings highlight crucial factors to be given due attention by managers, actuaries shareholders, portfolio managers and policy makers dealing with insurance companies in GCC markets.